Optimasi Proses Maserasi Vanili (Vanilla tahitensis JW Moore) Kering pada Produksi Ekstrak Vanili Menggunakan RSM - Muslim, Nizar Saeful; Hariyadi, Purwiyatno; Andarwulan, Nuri (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
The vanilla extraction process is widely practiced in Indonesia for Vanilla planifolia Andrews. However, with the growing popularity of Vanilla tahitensis JW Moore, this variety shows potential to replace Vanilla planifolia Andrews. As a result, an efficient and optimized extraction method is essential for Vanilla tahitensis JW Moore. In this study, Response Surface Methodology (RSM) was employed to optimize the maceration process, aiming to produce a vanilla extract with the most desirable characteristics. The key parameters evaluated included extraction effectiveness, final ethanol content, hedonic (aroma) test score, lightness, and total soluble solids. Based on the RSM results, the optimal conditions were determined to be a 60% ethanol concentration and a 28-day maceration time, with a desirability value of 0.786. Verification experiments validated these predictions, achieving an extraction effectiveness of 79.13%, ethanol content of 58.60%, a hedonic score of 4.36, lightness of 4.66, and total soluble solids of 20.28 °Brix. All outcomes fell within the 95% prediction interval. The vanilla extract produced meets the US-FDA standards, which require a minimum ethanol content of 35% v/v in the final product. The resulting extract is of high quality, with a rich vanillin aroma and a dark brown color that is well-accepted.